2016
DOI: 10.1088/0957-4484/27/8/085104
|View full text |Cite
|
Sign up to set email alerts
|

A multi-functional nanoplatform for tumor synergistic phototherapy

Abstract: Phototherapy, which mainly includes photothermal treatment (PTT) and photodynamic treatment (PDT), is a photo-initiated, noninvasive and effective approach for cancer treatment. The high accumulation of photosensitizers (PSs) in a targeted tumor is still a major challenge for efficient light conversion, to generate reactive oxygen species (ROS) and local hyperthermia. In this study, a simple and efficient hyaluronic acid (HA)-modified nanoplatform (HA-TiO2@MWCNTs) with high tumor-targeting ability, excellent p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…100 The up-conversion method of transforming NIR light into photoactivated chemotherapy at the lesion site has attracted much attention. 101 Xu et al prepared UCNPs with reversible charge and shrinking size to better promote cell internalization. 102 The hydrolysis of PEG-PAH-DMMA layer emerged UCNs loaded Pt(IV) prodrug by charge reversed in TME.…”
Section: Msr-ddss For Tumor Theranosticsmentioning
confidence: 99%
“…100 The up-conversion method of transforming NIR light into photoactivated chemotherapy at the lesion site has attracted much attention. 101 Xu et al prepared UCNPs with reversible charge and shrinking size to better promote cell internalization. 102 The hydrolysis of PEG-PAH-DMMA layer emerged UCNs loaded Pt(IV) prodrug by charge reversed in TME.…”
Section: Msr-ddss For Tumor Theranosticsmentioning
confidence: 99%
“…For instance, since they have thermal properties when exposed to infrared light, 43 their heating could be simultaneously used for diagnosis and disease treatments. Zhang et al 44 observed that CNT can be used as a photosensitive drug carrier both in vitro and in vivo to fight tumor cells by hyperthermia. Nanoparticles delivering hematoporphyrin monomethyl ether help to potentiate the antitumor effects of photodynamic therapy against breast cancer cells (MCF-7), increasing cancer cell death and exhibiting low toxicity in healthy tissues irradiated with laser light.…”
Section: ■ Applicability Of Cnts In Cancer Diagnosismentioning
confidence: 99%
“…Phototherapy as a new powerful cancer treatment technology has aroused tremendous concern in the light of its high selectivity, minimal invasiveness, remarkable reduced damage to normal tissues, and rather effective therapeutic efficacy compared with traditional methods. Phototherapy, generally including photothermal therapy (PTT) and photodynamic therapy (PDT), relies on light-harvesting material to generate adverse factor from laser energy to destroy cancer cells. PTT employs a photothermal agent to generate heat from near infrared (NIR) light energy, leading to thermal burn of cancer cells. However, PDT utilizes specific wavelength light to activate photosensitizer and transfer energy to molecular O 2 to produce reactive oxygen species (ROS), leading to strong oxidization damage of cancer cells .…”
Section: Introductionmentioning
confidence: 99%
“…Titanium-based materials have triggered an explosion of research interests in many fields such as catalysis, environment, aerospace, cosmetics, energy, and biomedicine. , In recent years, as the finest biocompatible metallic element in nature, titanium-based materials with high stability, nontoxicity, abundant storage, and unique photocatalytic activity have been successfully applied in cancer treatment, such as PDT, , PTT, sonodynamic therapy, and drug delivery. ,, Specially, titanium dioxide (TiO 2 ) as the inorganic photosensitizer has been extensively used in PDT of cancer because TiO 2 can generate photoinduced hole–electron pairs that can react with oxygen and water to produce ROS to kill cancer cells under light irradiation . Traditional TiO 2 -based PDT mainly employed ultraviolet (UV) light as a light source.…”
Section: Introductionmentioning
confidence: 99%